Determination of some trace elements in nails from population nearby oil fields in Southern Iraq - J. M. Al-Imarah, Faris; A. K. Garabedian , Seta (University of Thi-Qar Journal of Science, 2016)
Level of some trace elements Cadmium ( Cd), Cobalt (Co), Cupper (Cu),Nickel(Ni), Lead (Pb), and Zinc (Zn) in nails from 10 human being samples taken randomly from population nearby oil fields were examined from different subjects with respect to gender, age, smoking habit, the period of time living or working nearby the oil fields area and the health case were carried out using flame atomic absorption spectrophotometer (Sens AA GBC Scientific Equipment DUAL). Co showed the highest concentration (56.58µg/g) while no level were reported for Cu (ND) . The levels of the Co, Zn, and Ni elements were statistically higher in male subjects (56.58, 42.03, and 8.99) µg/g compared to 26.72, 36.20, and 0.73 µg/g for female subjects while Pb showed the highest level in female subjects 48.48 µg/g compared to 17.03 µg/g in male subjects. high levels of trace elements were observed in non-smokers, compared to smokers. The highest level of trace elements were appeared to those who are between (20-40) years old and also who are living period of time limited between (8-21) years nearby the oil field areas . Occupationally exposure showed no effect for trace elements accumulation in human finger nails compared to the time living nearby the oil field area that was limited between (9-10) years. One of the voluntaries who have a health problem hypertension as his case showed a highest level for the Pb element compared with the other hypertension case and the diabetes case, and the other voluntaries who have no problems.